CANNABIS USE PATTERN, DEPENDENCE AND WITHDRAWAL IN PATIENTS FROM AN ADDICTION CENTRE: A QUESTIONARE BASED SURVEY - V. Kshirsagar, Sharad.; Mangot, Ajish; Tembe, Dinesh (International Journal of Psychosocial Rehabilitation, 2020)
Cannabis use in previous researches has been linked with a increased incidence of various psychiatric disorders. Even withdrawal symptoms of cannabis use disorder are another aspect that has received attention in the past.To investigate use of cannabis and its depencdence along with withdrawal symptoms associated within a study sample obtained from treatment-seeking substance users at an addiction treatment centre.The study population is primarily those patients who have opioid dependence and/or alcohol dependence. Treatment is also provided at this centre in the form of medications, psychotherapy, and rehabilitation services. We included 80 subjects from the outpatient services and they were thoroughly assessed by a trained psychiatrists using questionnaires. All the data regarding demographic characteristic and details of substances of use were collected for each subject.The majority of our patients came for seeking treatment for opiod use related disorders. Substance dependence with tobacco was the commonest thing encountered in almost 95% of the cases. Cannabis related disorder showed craving (75%) as the most common feature. Overall we reported 62 subjects (75%) with cannabis use disorder in our study. Most common withdrawal features as apatite loss, weight loss, sleep related problems, anger, anxiety. The distress criteria was observed in only 31 subjects as having cannabis withdrawal according to this assessment.It is important to focus on cannabis and its related use disorders and further more such studies with a multicentric approach should be conducted to overcome the hindrances in treatment of cannabis use disorder patients.